Optimalisasi Penggunaan Mendeley sebagai Tools Manajemen Referensi Penulisan Karya Tulis Ilmiah Mahasiswa - Rosyida Nurul Anwar; Rohimatul Anwar (ServeInnovate: Journal of Applied Community Engagement (SJACE), 2026)
The rapid development of digital technology in education requires students to utilize various digital tools to support scientific writing, particularly in reference management and bibliography preparation. However, many students still experience difficulties in managing citations and references systematically because these processes are often performed manually. This community service program aimed to improve students’ ability to use Mendeley as a reference management application in scientific writing. The activity was conducted online through Microsoft Teams and involved 20 Open University students enrolled in the Research Methodology course. The program employed a participatory training approach consisting of lectures, demonstrations, hands-on practice, and mentoring. Training materials covered application installation, account creation, adding references to the Mendeley library, integration with Microsoft Word, citation management, and automatic bibliography generation. The results showed a substantial improvement in participants’ competencies. After the training, 90% of participants were able to install Mendeley independently, 85% could manage references in the library, 80% successfully integrated Mendeley with Microsoft Word, and 90% were able to generate citations automatically. The training also enhanced students’ awareness of digital literacy and academic integrity in scientific writing. Therefore, Mendeley can serve as an effective tool for improving students’ reference management skills in the era of educational digitalization.